ADAMTS13 activity and antigen during therapy and follow-up of patients with idiopathic thrombotic thrombocytopenic purpura: correlation with clinical outcome - Shangbin Yang; Ming Jin; Shili Lin; Spero Cataland; Haifeng Wu (Haematologica, 2011)
Background The assay for ADAMTS13 activity helps clinicians to confirm the clinical diagnosis of idiopathic thrombotic thrombocytopenic purpura. The clinical value of testing for the antigen level of ADAMTS13 protein is, however, less clear.Design and Methods In this study, both ADAMTS13 antigen and activity levels were measured in 835 sequential samples from 40 consecutive patients who were followed for an average of 29 months throughout the course of acute episode plasma exchange treatment and clinical remission.Results During acute episodes, ADAMTS13 activity was severely deficient while ADAMTS13 antigen levels were more variable, ranging from severely deficient to as high as within the reference range. A severe depletion of ADAMTS13 antigen level during acute disease was, however, statistically associated with disease mortality (P=0.0322). For patients who achieved initial clinical responses, ADAMTS13 antigen levels appeared to be restored faster than ADAMTS13 activity to the normal range. Further analysis demonstrated that the ADAMTS13 antigen level at the time of initial clinical recovery was significantly higher in the patients who subsequently achieved a sustained clinical remission than in the group who soon after had an exacerbation (P=0.0187).Conclusions Our data suggest that evaluation of ADAMTS13 antigen levels during the course of therapy and follow-up may offer additional useful information for the management of patients with thrombotic thrombocytopenic purpura.